2008
DOI: 10.1097/aln.0b013e31817f3de6
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transtracheal Lung Ventilation Using a Manual Respiration Valve

Abstract: This study demonstrated in vitro and in vivo in adult pigs that satisfactory lung ventilation can be assured with transtracheal ventilation through a 16-gauge cannula for a prolonged period of time if combined with a bidirectional manual respiration valve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…These findings were consistent with the results of our previous study [2] which demonstrated that airway anaesthesia for awake oral fibreoptic intubation achieved by atomised 2% lidocaine in the morbidly obese is an efficacious and safe technique (peak plasma lidocaine concentration 2.8 (0.8) lg.ml…”
Section: A Replysupporting
confidence: 82%
See 2 more Smart Citations
“…These findings were consistent with the results of our previous study [2] which demonstrated that airway anaesthesia for awake oral fibreoptic intubation achieved by atomised 2% lidocaine in the morbidly obese is an efficacious and safe technique (peak plasma lidocaine concentration 2.8 (0.8) lg.ml…”
Section: A Replysupporting
confidence: 82%
“…We continue to believe that one of the advantages of the atomised lidocaine technique is the rapidity at which the airway can be anaesthetised (< 5 min [1,2]). This may not only facilitate a rapid yet safe turnover of patients in a high-volume bariatric surgery program, but may be crucial in critical situations demanding prompt airway management [2].…”
Section: A Replymentioning
confidence: 99%
See 1 more Smart Citation
“…The authors previously measured pressures produced when using the Oxygen Flow Modulator alone [3]. They found that when gas flows of 15 l.min )1 were administered via a transtracheal catheter with all four holes of the Oxygen Flow Modulator open, the lowest pressure during expiration was 4.4 cmH 2 O.…”
mentioning
confidence: 99%
“…Since our publication, the authors have published at least two related articles [1,3], exploring some aspects of their original Enk Oxygen Flow Modulator (Cook Medical Inc., Bloomington, IN, USA) in combination with some aspects of our method, without mentioning our work. Yet Enk et al commented on our article from 2008 and their comment and our response were published [4,5].…”
mentioning
confidence: 99%